2018
DOI: 10.1016/j.jorganchem.2018.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Selective cytotoxicity of arene tricarbonylchromium towards tumour cell lines

Abstract: Metals are cytotoxic and could be harmful to human health; however, as their effects are dose dependent, some of them could be used in chemotherapy. In the present work, mineral chromium (VI) showed that it is cytotoxic on both tumour HeLa, and non-tumour ( The role of formyl and methoxy groups in arene tricarbonylchromium is shown in complexes acquiring the selective tumour cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The comparison of our results with those found in the literature is delicate because the cell types and exposure conditions were different. However, the IC 50 of Cr in HepaRG cells was close to those obtained for other human cell models. , For Co, there is a wide variation in IC 50 among published studies. , The IC 50 of Co in HepaRG cells was higher than that in keratinocytes for similar exposure conditions. For Ni, the only cytotoxicity study on human hepatocytes found in the literature presented an IC 50 slightly lower than ours for a 24 h exposure .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The comparison of our results with those found in the literature is delicate because the cell types and exposure conditions were different. However, the IC 50 of Cr in HepaRG cells was close to those obtained for other human cell models. , For Co, there is a wide variation in IC 50 among published studies. , The IC 50 of Co in HepaRG cells was higher than that in keratinocytes for similar exposure conditions. For Ni, the only cytotoxicity study on human hepatocytes found in the literature presented an IC 50 slightly lower than ours for a 24 h exposure .…”
Section: Discussionsupporting
confidence: 79%
“…However, the IC 50 of Cr in HepaRG cells was close to those obtained for other human cell models. 43,45 For Co, there is a wide variation in IC 50 among published studies. 58,59 The IC 50 of Co in HepaRG cells was higher than that in keratinocytes 42 for similar exposure conditions.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These finding could use the incorporation of CdCl 2 in organic compounds in order to create a tumour-specific toxicity. In fact a selective cytoxicity against cancer cell lines was obtained with chromium present in some arene tricarbonylchromium compounds vs the high toxicity of chromium in K 2 Cr 2 O 7 [55].…”
Section: Toxicity Testmentioning
confidence: 99%